2007
DOI: 10.1080/09064710600590861
|View full text |Cite
|
Sign up to set email alerts
|

Placement of nitrogen, phosphorus and potassium fertilizers by drilling in spring barley grown for malt without use of pesticides

Abstract: The increasing consumer demand for food products that are produced without the use of pesticides are reflected in action plans to reduce the use of pesticides in agriculture. Most of the barley (Hordeum vulgare L.) produced is used for pig feed but some is used for malting Á the primary step in the production of beer. The effects of fertilizer application method, type and rate on yield and grain quality were investigated in a malting barley crop without the use of pesticides. Twelve treatments, where single an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…1000 grain weight was statistically identical in T 6 and T 7 treatment by receiving 120% and 80% NPK briquette. Peterson [22] observed that placement of compound NPK fertilizer increased the grain yield and the quality parameters like grain size and grade. The effect of fertilizer placement on grain yield and quality decreased.…”
Section: Grain Weightmentioning
confidence: 99%
“…1000 grain weight was statistically identical in T 6 and T 7 treatment by receiving 120% and 80% NPK briquette. Peterson [22] observed that placement of compound NPK fertilizer increased the grain yield and the quality parameters like grain size and grade. The effect of fertilizer placement on grain yield and quality decreased.…”
Section: Grain Weightmentioning
confidence: 99%